3x+y = 2
2x -3y = 16
Find Solution...
y = 2-3x
2x -3(2-3x) = 16
2x -6 +9x = 16
11x= 22
x = 2
(Thanks for the correction, again.. many.. many years ago, but I do love the way the teacher put in answers that if you incorrectly made a step, you would get that result)
2007-03-21 01:53:14
·
answer #1
·
answered by Anonymous
·
2⤊
0⤋
2
2007-03-21 09:04:44
·
answer #2
·
answered by Anonymous
·
1⤊
0⤋
3x + y = 2
y = 2 - 3x
2x - 3y = 16
2x - 16 = 3y
2x - 16 = 3 * (2 - 3x)
2x - 16 = 6 - 9x
2x + 9x = 6 + 16
11x = 22
x = 22/11
x = 2 (A)
2007-03-21 08:59:32
·
answer #3
·
answered by Anonymous
·
1⤊
0⤋
3x+y = 2 and 2x-3y = 16
Therefore y = 2 - 3x, then substitute to other equation:
2x - 3(2-3x) = 16,
2x -6 + 9x = 16
-6 + 11x = 16
11x = 16 + 6
11x = 22
x = 22/11
therefore x = 2
Answer is a.2
2007-03-21 08:59:12
·
answer #4
·
answered by Anonymous
·
1⤊
0⤋
x = 2
y = -4
Just rearrange the first equation to give y = 2 - 3x and substitute in into the second one for y.
Subpacket should have added 6 to both sides in his last step to give-:
11 x = 22
therefore x = 2
2007-03-21 08:54:58
·
answer #5
·
answered by Doctor Q 6
·
1⤊
0⤋
3x + y =2 ----------------- (1)
2x - 3y = 16 --------------(2)
(1) x 3 becomes 9x + 3y=6 ------------------ (3)
(3)+(2) becomes 11x = 22
x = 22/11 = 2
2007-03-21 08:55:40
·
answer #6
·
answered by Anonymous
·
1⤊
0⤋
3x+y = 2
y = 2-3x
2x - 3y = 16
2x - 3(2-3x) = 16
2x- 6 + 9x = 16
11x = 22 !!!!!!!!!!!!!!!!!!!
x = 22/11 = 2 !!!!!!!!!!!!!!!
2007-03-21 08:57:56
·
answer #7
·
answered by cmbtkllr 2
·
1⤊
0⤋
y=-3x+2
2x-3(-3x+2)=16
2x+9x-6=16
11x-6=16
11x=22
x=2
y=-3(2)+2
y=-6+2
y=-4
The answer is a.
2007-03-21 09:35:11
·
answer #8
·
answered by Anonymous
·
0⤊
0⤋
but there r 2 variables!
2007-03-21 08:50:59
·
answer #9
·
answered by Really Confused 2
·
1⤊
0⤋
c
2007-03-21 08:53:52
·
answer #10
·
answered by nijas 2
·
0⤊
1⤋